PENGARUH METODE ROLE PLAYING TERHADAP KETERAMPILAN BERBICARA PADA MATAPELAJARAN BAHASA INDONESIA DI KELAS III SD RK NAMOPULI - Anumerta, Hutri Wangsa; Patri Janson Silaban; Darinda Sofia Tanjung; Juliana; Antonius Remigius Abi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to determine the effect of the role-playing method on students' speaking skills in the Indonesian language subject "Weather, Seasons, and Climate" in grade III of RK Namopuli Elementary School in the 2024/2025 academic year. This study was a quantitative study using experimental methods. The sample consisted of 21 students, using speaking skills tests, questionnaires, and documentation studies as data collection techniques. The results of the study showed that before the implementation of the role-playing method, students obtained an average score of 50.3, categorized as poor. Then, after the implementation of the role-playing method in learning, students' scores increased by 86.6, categorized as very good. Furthermore, a correlation test was conducted and obtained a value of 0.985 > 0.456 (r count ≥ r table) with a t-test indicating t count ≥ t table (7.311 ≥ 2.093), thus strengthening the decision that Ha was accepted. Thus, the role-playing learning method has a positive and significant effect on students' speaking skills.